User Experience Evaluation On The McDonald's Application Using The User Experience Questionnaire Method: Evaluasi User Experience Pada Aplikasi Mcdonald’s Menggunakan Metode User Experience Questionnaire - Fadhilah Shabuhalaika Aliyya; Aries Dwi Indriyanti (Universitas Negeri Surabaya, 2026)
In the rapidly evolving digital era, McDonald's launched a mobile app in 2019 as an effort to provide consumers with ease and convenience in accessing its fast food services. This app is designed to allow users to place orders, enjoy exclusive promotions, participate in loyalty programs, and obtain various other services more practically. However, the McDonald's app faces various technical issues that disrupt user convenience, such as transaction failures, login difficulties, and application instability, which impact the user experience and affect their satisfaction levels. This study involved 412 respondents who are active McDonald's app users. The evaluation results using the User Experience Questionnaire (UEQ) method showed that the McDonald's app obtained an average score that was categorized as